2019
DOI: 10.1016/j.fertnstert.2019.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Add-ons in the laboratory: hopeful, but not always helpful

Abstract: All the steps in an in vitro fertilization cycle are important but none more so than those that occur in the laboratory. To improve the chance of success, adjuncts, commonly referred to as 'add-ons', are offered. Yet as with other new interventions, add-ons in the laboratory require justification by well-designed studies prior to being offered as routine practice. Add-ons aim to improve the chance of a take-home baby, but, their safety and efficacy is less than clear. In addition, the financial burden from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“… Commercial interests may blur diagnostic needs and accuracy by offering non-validated tests called “adds on” which are unproven and costly. Some examples include the “embryo glue”; fertilome analysis; time-lapse imaging; routine freezing of all embryos and not doing fresh transfers; assisted hatching; and PGT/A for all [ 1 3 ]. US clinics, for example, offer PGT-A more frequently than the UK [ 29 ], and Australian IVF centers face a class action suit as a result of PGT-A [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“… Commercial interests may blur diagnostic needs and accuracy by offering non-validated tests called “adds on” which are unproven and costly. Some examples include the “embryo glue”; fertilome analysis; time-lapse imaging; routine freezing of all embryos and not doing fresh transfers; assisted hatching; and PGT/A for all [ 1 3 ]. US clinics, for example, offer PGT-A more frequently than the UK [ 29 ], and Australian IVF centers face a class action suit as a result of PGT-A [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although IVF clinics seek to help patients increase their chances of having a baby by offering add-ons, the evidence base for their effectiveness is variable but generally limited. Both the Human Fertilisation and Embryology Authority (HFEA), which is the UK regulator of IVF, and recent scientific reviews have found that there is limited high-quality evidence to support the use of add-ons in routine practice (Armstrong et al, 2019;Farquhar, 2019;Harper et al, 2017;HFEA 2018).…”
mentioning
confidence: 99%
“…There was agreement that many patients find the prospect of customised care attractive. The debate is whether the availability of customisation options is actually beneficial if the options may not improve outcomes, or could be confusing for patients (Armstrong et al, 2019, Wilkinson, et al, 2019b. This is emphasised by recent qualitative work suggesting that many patients attempt to identify which combination of the many options offered will 'work for them' (Perrotta and Hamper, 2021).…”
Section: Research and Evidencementioning
confidence: 99%